Contributors to frequent telehealth alerts including false alerts for patients with heart failure: A mixed methods exploration - Radhakrishnan, K.; Bowles, K.; Zettek-Sumner, A. (Applied Clinical Informatics, 2013)
Background: Telehealth data overload through high alert generation is a significant barrier to sustained adoption of telehealth for managing HF patients.Objective: To explore the factors contributing to frequent telehealth alerts including false alerts for Medicare heart failure (HF) patients admitted to a home health agency.Materials and Methods: A mixed methods design that combined quantitative correlation analysis of patient characteristic data with number of telehealth alerts and qualitative analysis of telehealth and visiting nurses’ notes on follow-up actions to patients’ telehealth alerts was employed. All the quantitative and qualitative data was collected through retrospective review of electronic records of the home heath agency.Results: Subjects in the study had a mean age of 83 (SD = 7.6); 56% were female. Patient co-morbidities (p<0.05) of renal disorders, anxiety, and cardiac arrhythmias emerged as predictors of tele-health alerts through quantitative analysis (n = 168) using multiple regression. Inappropriate tele-health measurement technique by patients (54%) and home healthcare system inefficiencies (37%) contributed to most telehealth false alerts in the purposive qualitative sub-sample (n = 35) of patients with high telehealth alerts.Conclusion: Encouraging patient engagement with the telehealth process, fostering a collaborative approach among all the clinicians involved with the telehealth intervention, tailoring tele-health alert thresholds to patient characteristics along with establishing patient-centered telehealth outcome goals may allow meaningful generation of telehealth alerts. Reducing avoidable tele-health alerts could vastly improve the efficiency and sustainability of telehealth programs for HF management.Citation: Radhakrishnan K, Bowles K, Zettek-Sumner A. Contributors to frequent telehealth alerts including false alerts for patients with heart failure: A mixed methods exploration. Appl Clin Inf 2013; 4: 465–475http://dx.doi.org/10.4338/ACI-06-RA-0039
Keywords: Telehealth alerts; false alerts; heart failure; home health nursing